Testis developmental related gene 1 promotes non-small-cell lung cancer through the microRNA-214-5p/Krüppel-like factor 5 axis. Issue 1 (1st January 2022) - Lu, Xudong; Zhao, Nian; Duan, Guangjun; Deng, Zhiyong; Lu, Yimin
ABSTRACT: Non-small-cell lung cancer (NSCLC) is a frequent malignancy and has a high global incidence. Long noncoding RNAs (lncRNAs) are implicated in carcinogenesis and tumor progression. LncRNA testis developmental related gene 1 (TDRG1) plays a pivotal role in many cancers. This study researched the biological regulatory mechanisms of TDRG1 in NSCLC. Gene expression was assessed by reverse transcriptase quantitative polymerase chain reaction (RT–qPCR). Changes in the NSCLC cell phenotypes were examined using 5-ethynyl-2ʹ-deoxyuridine (EdU), cell counting kit-8 (CCK-8), wound healing, flow cytometry, and Transwell assays. The binding capacity between TDRG1, microRNA-214-5p (miR‑214-5p), and Krüppel-like factor 5 (KLF5) was tested using luciferase reporter and RNA immunoprecipitation (RIP) assays. In this study, we found that TDRG1 was upregulated in NSCLC samples. Functionally, TDRG1 depletion inhibited NSCLC cell growth, migration, and invasion and accelerated apoptosis. In addition, TDRG1 interacted with miR-214-5p, and miR-214-5p directly targeted KLF5. The suppressive effect of TDRG1 knockdown on NSCLC cellular processes was abolished by KLF5 overexpression. Overall, TDRG1 exerts carcinogenic effects in NSCLC by regulating the miR-214-5p/KLF5 axis. Flow Sheet Abstract: uf0001